Impact of Helicobacter pylori infection on iron deficiency anemia in children: a systematic review and meta-analysis with early intervention implications - Wang, Ziteng; Tan, Wentao; Xiong, Huanhuan; Huang, Jiali; Wei, Herui; Li, Mengqi; Luo, Jing; An, Wen; He, Lingling; Ma, Jiali; Xiao, Fan; Wei, Hongshan (Frontiers in Microbiology, 2025)
BackgroundThis study investigates the association between Helicobacter pylori (H. pylori) infection and iron deficiency (ID) as well as its potential link to iron deficiency anemia (IDA) in children.MethodsAs of August 2024, we conducted a comprehensive literature review using the Embase, PubMed, Web of Science, Ovid Medline, and Cochrane databases to compare the risk of IDA in patients with and without H. pylori infection. The Newcastle-Ottawa Quality Assessment Scale was used to assess the methodological quality of the included studies. Odds ratios (ORs) and 95% confidence intervals (CIs) were extracted from the studies, and data were transformed for meta-analysis. Heterogeneity was evaluated using the I2statistic, and homogeneity was tested with the chi-square test. If the I2 value was 50% or greater, a random-effects model was applied; if the I2 value was below 50%, a fixed-effects model was used. The meta-regression was performed to explore the potential sources of heterogeneity. Additionally, a meta-analysis was conducted to assess the changes in hemoglobin and ferritin concentrations before and after H. pylori eradication.ResultsWe analyzed data from patients across 13 countries. Our findings reveal that individuals infected with H. pylori have a higher likelihood of developing ID compared to those uninfected, with an OR = 1.52 (p < 0.00001, 95% CI 1.32–1.74, I2 = 44%). The risk of IDA is also higher in patients with H. pylori, with an OR = 1.83 (p = 0.05, 95% CI 1.01–3.33, I2 = 67%). Conversely, the overall effect of H. pylori infection on anemia is minimal, with an OR = 0.94 (p = 0.64, 95% CI 0.73–1.21, I2 = 96%). Meta-regression results suggest that age is the main source of heterogeneity. A meta-analysis of treatment-related randomized controlled trials revealed that combining iron supplementation with H. pylori eradication therapy significantly raised ferritin levels, with an SMD (Standardized Mean Difference) = 0.86 (p = 0.02, 95% CI 0.14–1.57, I2 = 89%). Hemoglobin levels also showed an increase, with an SMD = 0.47 (p = 0.04, 95% CI 0.01–0.93, I2 = 75%).ConclusionIn children, there is a significant association between H. pylori infection and both ID and IDA. Additionally, the eradication of H. pylori has been shown to lead to an improvement in iron stores.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=426395. PROSPERO ID: CRD42023426395.